2019
DOI: 10.1038/s41467-019-13864-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyanions provide selective control of APC/C interactions with the activator subunit

Abstract: Transient interactions between the anaphase-promoting complex/cyclosome (APC/C) and its activator subunit Cdc20 or Cdh1 generate oscillations in ubiquitylation activity necessary to maintain the order of cell cycle events. Activator binds the APC/C with high affinity and exhibits negligible dissociation kinetics in vitro, and it is not clear how the rapid turnover of APC/C-activator complexes is achieved in vivo. Here, we describe a mechanism that controls APC/C-activator interactions based on the availability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Through RNA mimicry, viral RNAs can mimic the shape of cellular tRNAs ( Colussi et al, 2014 ). RNA can also mimic the shape of proteins and protein interaction surfaces ( Athanassiou et al, 2004 ; Shao and Hegde, 2016 ; Mizrak and Morgan, 2019 ). Here, we found that the network structure and morphogenesis of the tubular ER that is generated by proteins and lipids can be mimicked by phase-separated condensates formed by protein and RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Through RNA mimicry, viral RNAs can mimic the shape of cellular tRNAs ( Colussi et al, 2014 ). RNA can also mimic the shape of proteins and protein interaction surfaces ( Athanassiou et al, 2004 ; Shao and Hegde, 2016 ; Mizrak and Morgan, 2019 ). Here, we found that the network structure and morphogenesis of the tubular ER that is generated by proteins and lipids can be mimicked by phase-separated condensates formed by protein and RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitylation of securin and Clb5 by APC/C Cdc20 is more processive than that with APC/C Cdh1 , while Hsl1 is more processively modified by APC/C Cdh1 (ref 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…1b), a late mitotic substrate that is targeted primarily by APC/C Cdh1 in vivo 29 . The Hsl1 D box is known to have an ideal consensus sequence that binds tightly to APC/C Cdh1 , resulting in highly processive modification 19,30 . We found that the Hsl1 D box binds the Cdh1 WD40 domain with a dissociation constant (KD) of 4.0 µM (Fig.…”
Section: Analysis Of Degron Affinity By Ensemble Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study by Mizrak and Morgan (2019) implicated binding of the APC/C to polyanions, including nucleic acid polymers which are components of nucleosomes, as a mechanism to regulate the dissociation of CDC20 and CDH1 from the APC/C. Using lysates from Saccharomyces cerevisiae to perform in vitro experiments, they show that single-stranded DNA and RNA of about 75 base pairs, as well as polyphosphate species, promote the dissociation of CDC20 and CDH1 from the APC/C.…”
Section: Apc/c Regulates Chromatinmentioning
confidence: 99%